DISRUPTIONS IN PROTEIN METABOLISM AND THE RESULTING DISEASES - Umurov Erkin Utkirovich, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract   Protein metabolism is a vital process for maintaining cellular structure  and function,  enzyme  activity,  and  immune  system  integrity.  Disruptions  in  protein metabolism can lead to various diseases, including protein-energy malnutrition, liver and kidney dysfunction, and muscle disorders. Imbalances in protein synthesis and degradation,  along  with  deficits  in  essential  amino  acids,  can  cause  significant metabolic  consequences.  This  article  explores  the  mechanisms  behind  protein metabolism, the pathophysiology of its disruption, and the diseases associated with these disturbances.